2007
DOI: 10.1111/j.1365-2249.2007.03346.x
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4-dependent recognition of structurally different forms of chemically synthesized lipid As of Porphyromonas gingivalis

Abstract: SummaryPorphyromonas gingivalis is a Gram-negative anaerobic oral black-pigmented bacterium closely associated with chronic periodontitis. Lipopolysaccharide (LPS) derived from P. gingivalis is shown to be unusual because the LPS contains a greater number of lipid A species, such as tri-, tetra-, and/or pentaacylated lipid As. In this study, a lipid A possessing penta-fatty acyl chains derived from P. gingivalis strain 381 (compound PG-381-5FA) was synthesized, and examined for its immunobiological activities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 28 publications
(51 reference statements)
2
41
2
Order By: Relevance
“…These results support the concept that pathogens evolved to manipulate innate immunity for promoting their adaptive fitness and, consequently, their capacity to cause disease (Finlay & McFadden 2006). The chemical and biological properties of P. gingivalis LPS and its lipid A are different from those of enterobacterial LPS and their lipid A (Ogawa 1994), and different forms of P. gingivalis lipid functionally interact with only TLR4 (Sawada et al 2007). Milward et al (Milward et al 2007) demonstrated that Fusobacterium nucleatum and Porphyromonas gingivalis have differential effects at the molecular level on oral epithelial cells and that their differences in activating NF-B nuclear translocation in oral epithelial cells may at least in part be responsible for the change in dynamics and kinetics of downstream gene expression.…”
Section: Bacterial Specificitiessupporting
confidence: 61%
“…These results support the concept that pathogens evolved to manipulate innate immunity for promoting their adaptive fitness and, consequently, their capacity to cause disease (Finlay & McFadden 2006). The chemical and biological properties of P. gingivalis LPS and its lipid A are different from those of enterobacterial LPS and their lipid A (Ogawa 1994), and different forms of P. gingivalis lipid functionally interact with only TLR4 (Sawada et al 2007). Milward et al (Milward et al 2007) demonstrated that Fusobacterium nucleatum and Porphyromonas gingivalis have differential effects at the molecular level on oral epithelial cells and that their differences in activating NF-B nuclear translocation in oral epithelial cells may at least in part be responsible for the change in dynamics and kinetics of downstream gene expression.…”
Section: Bacterial Specificitiessupporting
confidence: 61%
“…5B). The lack of interaction is most likely due to significant differences in the structures of LPSs derived from P. gingivalis and E. coli (41,57,76). Again, unequivocal binding was noted mainly for PK, but only at half the capacity observed for FimA.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, dephosphorylation of lipid A by P. gingivalis phosphatases prevents TLR4 activation and promotes resistance to cationic antimicrobial peptides (48). Other reports, however, describe P. gingivalis LPS preparations as a highly heterogeneous mixture of different types of lipid A species with differential levels of stimulatory potency in their effects on TLR2 and TLR4 (10,14,49). In addition, a few studies demonstrated that TLR2 activity can be attributed to P. gingivalis lipoproteins (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%